Exploring online customer engagement with hospitality products and its relationship with involvement, emotional states, experience and brand advocacy - Bilro, R.G.; Loureiro, S. M. C.; Guerreiro, J. (Journal of Hospitality Marketing and Management, 2019)
Opinions published online about a given experience are known to influence consumers’ decisions. However, such opinions reflect different degrees of engagement which may affect the decisions in different forms. The aim of this study is to analyze the dimensions of online customer engagement and associated concepts (involvement,emotional states, experience and brand advocacy) in customers’ online reviews through text-mining and sentiment analysis trends. The current study focuses on Yelp.com comments and includes a random sample of 15,000 unique reviews of restaurants, hotels and nightlife entertainment in eleven cities in the USA. A customer engagement dictionary is created, based on previously validated scales and extended using WordNet 2.1. The research findings reveal a high impact of the engagement cognitive processing dimension and hedonic experience on customers’ review endeavor. Results further indicate that customers seem to be more engaged in positively advocating a company/brand than the contrary. Companies that listen to such feedback may be more able to align with consumers’ expectations and, therefore, have a better competitive advantage in the market.